2017
DOI: 10.1002/2016gl071584
|View full text |Cite
|
Sign up to set email alerts
|

Snow‐(N)AO relationship revisited over the whole twentieth century

Abstract: Several studies suggest that the Siberian snow cover in fall is a source of predictability of the Arctic Oscillation (AO) in winter. Although a plausible dynamical mechanism was proposed, the robustness of this relationship was recently challenged. Here we use two atmospheric reanalyses to revisit the snow‐AO relationship and its modulation across the whole twentieth century. While our results support a stratospheric pathway mechanism, they show that the snow‐AO relationship has only emerged in the 1970s and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…We would like to emphasise that whilst the inter‐decadal differences in NAO skill are, by themselves, only marginally statistically significant (Weisheimer et al, ), the variations in skill strongly co‐vary with statistics of the general circulation itself (examples of which can be found in e.g. Minobe, ; Hoerling et al, ; Derome et al, ; Fletcher and Saunders, ; Greatbatch and Jung, ; Douville et al, ; Hegerl et al, ; Huang et al, ) suggesting that such differences are indeed physically based. In particular, the temporal skill evolution of the NAO co‐varies with changes in the skill of the Pacific–North America (PNA) pattern that are highly statistically significant and relate to changes in the ENSO–North Pacific teleconnections (O'Reilly et al, ; O'Reilly, ).…”
Section: Discussionmentioning
confidence: 99%
“…We would like to emphasise that whilst the inter‐decadal differences in NAO skill are, by themselves, only marginally statistically significant (Weisheimer et al, ), the variations in skill strongly co‐vary with statistics of the general circulation itself (examples of which can be found in e.g. Minobe, ; Hoerling et al, ; Derome et al, ; Fletcher and Saunders, ; Greatbatch and Jung, ; Douville et al, ; Hegerl et al, ; Huang et al, ) suggesting that such differences are indeed physically based. In particular, the temporal skill evolution of the NAO co‐varies with changes in the skill of the Pacific–North America (PNA) pattern that are highly statistically significant and relate to changes in the ENSO–North Pacific teleconnections (O'Reilly et al, ; O'Reilly, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the low observation density in the first half of the twentieth century and a drop of the global number of assimilated observations before the 1940s (Compo et al, 2011;Douville et al, 2017), the 20CR2 product is deemed probably unreliable for the early part of the record (Krueger et al, 2013). The 20CR2 reanalysis is produced by assimilating surface pressure observations along with a prescribed SST boundary condition.…”
Section: Data Setsmentioning
confidence: 99%
“…For example, in Fletcher et al (), they reported on the response of a stratospheric resolving model to a snow perturbation; however, this model had a low decorrelation time in the stratosphere, with a decorrelation timescale of around 9–11 days between 100 hPa and 10 hPa, which is about a half of what is seen in ERA‐Interim and simulated by their other low‐top model (see their Figure 12). Furthermore, Peings et al () and Douville et al () found that the observed link is unstable during the twentieth century and proposed that the snow‐AO relation can be modulated by the QBO.…”
Section: Introductionmentioning
confidence: 99%